Shared challenges to the control of complex intracellular neglected pathogens - Perez, Rebecca Lynn; Chase, Jemima; Tanner, Rachel (Frontiers in Public Health, 2024)
The complex intracellular pathogens Mycobacterium tuberculosis, Mycobacterium leprae, Leishmania spp., and Burkholderia pseudomallei, which cause tuberculosis, leprosy, leishmaniasis, and melioidosis respectively, represent major health threats with a significant global burden concentrated in low- and middle-income countries. While these diseases vary in their aetiology, pathology and epidemiology, they share key similarities in the biological and sociodemographic factors influencing their incidence and impact worldwide. In particular, their occurrence in resource-limited settings has important implications for research and development, disease prevalence and associated risk factors, as well as access to diagnostics and therapeutics. In accordance with the vision of the VALIDATE (VAccine deveLopment for complex Intracellular neglecteD pAThogeEns) Network, we consider shared challenges to the effective prevention, diagnosis and treatment of these diseases as shaped by both biological and social factors, illustrating the importance of taking an interdisciplinary approach. We further highlight how a cross-pathogen perspective may provide valuable insights for understanding and addressing challenges to the control of all four pathogens.